Flow Cytometry Sorting to Separate Viable Giant Viruses from Amoeba Co-culture Supernatants - Khalil, Jacques Y. B.; Langlois, Thierry; Andreani, Julien; Sorraing, Jean-Marc; Raoult, Didier; Camoin, Laurence; La Scola, Bernard (Frontiers in Cellular and Infection Microbiology, 2017)
Flow cytometry has contributed to virology but has faced many drawbacks concerning detection limits, due to the small size of viral particles. Nonetheless, giant viruses changed many concepts in the world of viruses, as a result of their size and hence opened up the possibility of using flow cytometry to study them. Recently, we developed a high throughput isolation of viruses using flow cytometry and protozoa co-culture. Consequently, isolating a viral mixture in the same sample became more common. Nevertheless, when one virus multiplies faster than others in the mixture, it is impossible to obtain a pure culture of the minority population. Here, we describe a robust sorting system, which can separate viable giant virus mixtures from supernatants. We tested three flow cytometry sorters by sorting artificial mixtures. Purity control was assessed by electron microscopy and molecular biology. As proof of concept, we applied the sorting system to a co-culture supernatant taken from a sample containing a viral mixture that we couldn’t separate using end point dilution. In addition to isolating the quick-growing Mimivirus, we sorted and re-cultured a new, slow-growing virus, which we named ‘Cedratvirus’. The sorting assay presented in this paper is a powerful and versatile tool for separating viral populations from amoeba co-cultures and adding value to the new field of flow virometry.